Investigating the Gender Approach Based on the Theme of Betrayal and Infidelity - Mahmood Foroutan Mehraderani; Reza Ruhani; Reza Shajari (تاریخ ادبیات)
The role of society and political factors regarding the differences of human language is undeniable, and such issues, together with biological factors, forces, and multiple impositions, causes the differences between male and female languages. This difference, along with the theme of betrayal in poets' poems, has created remarkable examples. In this research, considering the betrayal component and based on Robin Lakoff's opinions, an attempt has been made to introduce the languages of four contemporary poets, and finally to compare with each other. Such an approach leads to the recognition of the differences in the views on woman and man, and in general, the perception of these poets about the relationship between the earthly lovers centered on betrayal. The findings of this research indicate that the languages of Farrokhzad and Behbahani are very clear in the use of color words, promise words, etc. Compared to these two, the languages of Shahryar and Mo'ayyeri, due to the use of masculine language, are indifferent toward these elements. The type of gender perspective and attention to feminist issues is also more obvious in the poems of Farrokhzad and Behbahani, and besides recounting issues related to infidelity, they try to change the audiences' views toward woman. But in comparison with these two, in Shahryar's poems, the components of betrayal and disloyalty have never caused the gender distinction, or the superiority of man over woman. On the other hand, a gender distinction can be seen in the poems of Rahi Mo'ayyeri.